PENGARUH VARIABEL SHAKING TABLE TERHADAP KADAR DAN RECOVERY PENCUCIAN BIJIH TIMAH PRIMER PT MENARA CIPTA MULIA KABUPATEN BELITUN VARIABEL SHAKING TABLE TERHADAP KADAR DAN RECOVERY PENCUCIAN BIJIH TIMAH PRIMER PT MENARA CIPTA MULIA KABUPATEN BELITUNG TIMUR - Dihan Fauzan; Janiar Pitulima; Delita Ega Andini (MINERAL, 2018)
The process of washing primary tin ore at PT Menara Cipta Mulia in the final stage uses gravity concentration method to separate mineral cassiterite from its impurity minerals. The separation process uses a shaking table with 2 stages of washing to minimize the waste of valuable minerals (losses). In the initial stages of washing, the primary shaking table and finishing stages use secondary shaking table. Currently the use of shaking tables at PT MCM does not have default standards in operation and still uses trial and error. Reseach method by varying the slope variables of the table in the primary tool shaking table 4 variations, namely 0.95°, 1.27°, 1.59°, 1.91° and washing water velocity of 3 variations, namely 0.6 m/s, 0.9 m/s, 1.2 m/s while on secondary shaking table tools 3 variations are slope that is 0.64°, 0.95°, 1.27° and washing water velocity of 3 variations is 0.6 m/s, 0.9 m/s, 1.2 m/s with this variable variation, the sample is obtained for the grade test and recovery calculation. The optimal results on the primary shaking table were at 1.27 degrees with an average recovery of 56.43% and grade Sn of 51.28%. Optimal water velocity is 0.9 m/s with an average recovery of 50.97% and grade Sn of 52.19%. While the optimal results for the secondary shaking table are at a slope of 0.64 degrees with recovery averaging 40.88% and grade of 71.64% with an optimal water velocity is 0.9 m/s with an average recovery of 32.24% with concentrate grade Sn 72.18%. The greater the value of the slope angle and water velocity be used, the smaller the recovery of washing tin ore produced but the smaller the recovery value indicates the higher the concentration of the resulting concentrate.